Anatomical-Based Filler Injection Diagnosis to Treatment Techniques: Infraorbital Groove and Hollowness - Hong, Gi-Woong; Choi, Wonseok; Yoon, Song-Eun; Wan, Jovian; Yi, Kyu-Ho (Life (Basel, Switzerland), 2025)
Infraorbital groove and hollowness are common aging-related anatomical changes in the periorbital region, leading to a sunken and tired appearance. These conditions are caused by the progressive loss of volume in the deep fat pads, including the sub-orbicularis oculi fat (SOOF) and malar fat, along with skin thinning and decreased elasticity. Filler injections, particularly hyaluronic acid-based fillers, are the preferred treatment to restore volume and smooth the under-eye area. Proper diagnosis, understanding of anatomical variations, and accurate injection techniques are essential to avoid complications and achieve natural, esthetically pleasing outcomes. Treatments should consider the patient’s unique anatomy and potential adjunctive procedures to ensure balanced and harmonious facial rejuvenation.